Lymphomatoid papulosis/Other primary cutaneous lymphomas. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Lymphomatoid papulosis (LyP) is a primary lymphoma of the skin with a benign prognosis; it is rare in children and must be differentiated from other primary cutaneous nodular lymphomas, even more rare in children. However, the latter require, unlike LyP, accurate staging and appropriate therapy. On the other hand, the differential diagnosis does not arise with mycosis fungoides, which begins with not infiltrated patches.